2018
DOI: 10.1371/journal.pone.0199010
|View full text |Cite
|
Sign up to set email alerts
|

MeDIP combined with in-solution targeted enrichment followed by NGS: Inter-individual methylation variability of fetal-specific biomarkers and their implementation in a proof of concept study for NIPT

Abstract: DNA methylation is the most characterized epigenetic process exhibiting stochastic variation across different tissues and individuals. In non-invasive prenatal testing (NIPT) fetal specific methylated regions can potentially be used as biomarkers for the accurate detection of fetal aneuploidies. The aim of this study was the investigation of inter-individual methylation variability of previously reported fetal-specific markers and their implementation towards the development of a novel NIPT assay for the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The decision on prenatal testing has to weigh the benefits for the families and the methodological limitations. With the diagnostic implementation of high-throughput and deep-sequencing molecular approaches in methylation and prenatal testing 43,47,48 , further improvement of testing can be expected. However, the suitability of each test has to be monitored, and each test needs appropriate validation.…”
Section: Discussionmentioning
confidence: 99%
“…The decision on prenatal testing has to weigh the benefits for the families and the methodological limitations. With the diagnostic implementation of high-throughput and deep-sequencing molecular approaches in methylation and prenatal testing 43,47,48 , further improvement of testing can be expected. However, the suitability of each test has to be monitored, and each test needs appropriate validation.…”
Section: Discussionmentioning
confidence: 99%
“…Poor prognosis, organ abnormalities, mental retardation, and growth retardation are the common features. [3][4][5] Prenatal diagnosis is based on providing genetic counseling for highrisk pregnant females, with further applications of modern biology, biochemistry, immunogenetics, cytogenetics, and molecular genetics techniques to perform maternal or embryo/fetal testing to achieve the diagnosis of chromosomal abnormalities. Traditionally, among the procedures of prenatal diagnosis, the most commonly used and effective method of prenatal diagnosis for fetuses in mid-term pregnancy is amniocentesis and karyotyping of amniotic fluid…”
Section: Discussionmentioning
confidence: 99%
“…The NGS represented by NIPT, through the noninvasive method, amplifying and counting of the free fetal DNA fragments in the maternal plasma, is used for detection of the genetic material nucleotides to realize the bioinformatics interpretation of the DNA fragments. 2 , 3 , 6 NIPT is currently regarded as a breakthrough method for the detection of fetal chromosomal aneuploidy. A series of clinical verifications have confirmed that NIPT has high sensitivity and specificity for trisomy 21 and trisomy 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations